Phaco capsulotomy in intumescent cataract - Mahalingam, Prabhushanker; Sambhav, Kumar (Nepalese Journal of Ophthalmology, 2014)
No Abstract DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11718 Nepal J Ophthalmol 2014; 6(12): 242-243